AN ERROR ANALYSIS IN USING CORRELATIVE CONJUCTION IN EXPRESSING LIKE AND DISLIKE AT THE EIGHTH GRADE OF SMP NEGERI 3 SITOLU ORI IN 2023/2024 - TELAUMBANUA, MEI HARTATI; TELAUMBANUA, YASMINAR AMAERITA; ZEBUA, ELWIN PIARAWAN; WARUWU, YAREDI (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2024)
The purposes of the research is to analyze the types of errors and find out the sources of errors made by the eighth-grade students of SMP Negeri 3 Sitolu Ori on using correlative conjuction in expressing like and dislike. The method used in the research was descriptive qualitative. The analysis of the data was conducted by following the procedures of error analysis namely collect data, identification of error, description of error, explanation of error and evaluation of error. Furthermore, the informant of the research is class VIII–A students of SMP Negeri 3 Sitolu Ori which consisted of 20 students. The data will collect by took the video documentation of student speaking about expressing like and dislike and interview both of students and the English Teacher. Based on the explanation above, the researcher interests to do a research by entitling, “An Error Analysis on Using Correlative Conjuction In Expressing Like And Dislike At The Eighth Grade of SMP Negeri 3 Sitolu Ori in 2023/2024”